KEANEKARAGAMAN PALMAE DI DESA TANTA KABUPATEN TABALONG SEBAGAI BAHAN PENGAYAAN MATA KULIAH PHANEROGAMAE BERBENTUK E-BOOKLET - sabara, Yosia Christina; Noorhidayati, Noorhidayati; Mahrudin, Mahrudin (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The diversity of familia Palmae in Tanta Village, Tabalong Regency is one of the local potentials that can be used as enrichment for Phanerogamae courses. This research aims (1). Describe the Diversity of Palmae in the village of Tanta, Tabalong Regency. (2). Describe the validity of the Palmae Diversity E-Booklet in Tanta Village, Tabalong Regency as an enrichment of the Arecaceae sub-concept in the Phanerogamae course. (3). Describe the legibility test of the E-Booklet diversity of Palmae in Tanta Village, Tabalong Regency as an enrichment of the Arecaceae sub-concept in the Phanerogamae course. Research and development refers to the Borg and Gall (1989) model. The results obtained 9 species, namely: Livistona rotundifolia Mart (Fan Palm) as many as 15, Caryota monostachya (Fishtail Palm) as many as 37, Arenga pinnata Merr (Aren) as many as 73, Salacca edulis Reinw (Salak) as many as 71, Metroxylon sago Rottb (Rumbia ) of 45, Cocos nucifera L (Coconut) of 68, Areca catechui L (Areca nut) of 18, Elaeis gueneensis Jaqc (Palm oil) of 15, and Calamus manan (Manau rattan) of 26. The validity test of the E-Booklet obtained very high results. valid with a score of (3.59), the E-Booklet readability test obtained very good results with a score of (89.31%), based on this the Palmae Diversity E-Booklet in Tanta Village, Tabalong Regency can be used as enrichment material for Phanerogamae courses.